2014
DOI: 10.1016/j.ijid.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-insensitive Acinetobacter baumannii in Egypt

Abstract: The blaADC-, blaTEM-, blaPER-, blaOXA-23-, and blaGES-like genes were found to be the most prevalent types of β-lactamase-encoding gene in A. baumannii collected from Egypt. A high level of carbapenem resistance is mediated by blaOXA-23, blaOXA-24, and blaOXA-58 (minimum inhibitory concentration (MIC) 32 to >256μg/ml), and a low level of carbapenem resistance is mediated by blaGES (MIC 4-16μg/ml) and by up-regulation of ISAba1-OXA-51 (MIC 1-4μg/ml). Class B MBL was not identified to play a role in carbapenem r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
90
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 42 publications
38
90
8
Order By: Relevance
“…The bla OxA-23 was previously described in the university hospital Sahloul in Tunisia [3] and it was chromosome located. However, numerous other studies showed the plasmid location of the bla OxA-23 gene [6,24].So, a possible transfer of this strain from the Sahloul university hospital to the neonatology center is strongly probable.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The bla OxA-23 was previously described in the university hospital Sahloul in Tunisia [3] and it was chromosome located. However, numerous other studies showed the plasmid location of the bla OxA-23 gene [6,24].So, a possible transfer of this strain from the Sahloul university hospital to the neonatology center is strongly probable.…”
Section: Discussionmentioning
confidence: 88%
“…OXA-type carbapenemases have predominated in A. baumannii, especially worldwide outbreaks of OXA-23 [1]. Recently the GES-1-like carbapenemases have also been reported for A. baumannii [9,14,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations